2007
DOI: 10.1111/j.1348-0421.2007.tb03974.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Cytolethal Distending Toxin (cdt) Gene‐Based Species‐Specific Multiplex PCR Assay for the Identification of Campylobacter Strains Isolated from Poultry in Thailand

Abstract: We have recently developed a cytolethal distending toxin (cdt) gene‐based species‐specific multiplex PCR assay for identifying Campylobacter jejuni, C. coli and C. fetus. In the present study, the applicability of this assay was evaluated with 34 Campylobacter‐like organisms isolated from poultry in Thailand for species identification and was compared with other assays including API Campy, 16S rRNA gene sequence, and hippuricase (hipO) gene detection. Of the 34 strains analyzed, 20, 10 and 1 were identified as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
39
0
4

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 35 publications
2
39
0
4
Order By: Relevance
“…Briefly, heat-denatured genomic DNA (300 ng) was applied to a GeneScreen Plus (DuPont, Boston, MA, USA). The membranes were hybridized with cdt gene probes under highly stringent conditions as described previously (18). The cdtA, cdtB, and cdtC gene probes for C. jejuni, C. coli, and C. fetus were amplified by PCR using the primer sets described above.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Briefly, heat-denatured genomic DNA (300 ng) was applied to a GeneScreen Plus (DuPont, Boston, MA, USA). The membranes were hybridized with cdt gene probes under highly stringent conditions as described previously (18). The cdtA, cdtB, and cdtC gene probes for C. jejuni, C. coli, and C. fetus were amplified by PCR using the primer sets described above.…”
Section: Methodsmentioning
confidence: 99%
“…PCR for hipO gene detection and 16S rRNA gene amplification was performed as described previously (17,18). The PCR primers and conditions used in this study are summarized in Table 1.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Asakura et al [2] observed that cdt genes were universally distributed in C. jejuni, C. coli and C. fetus in a species-specific manner. Based on this finding, a cdt genebased species-specific multiplex PCR targeting either cdtA, cdtB, or cdtC gene has been developed [3] and evaluated for the accuracy of the species identification with a large number of isolates of C. jejuni, C. coli and C. fetus of clinical or animal origin [14,30].…”
mentioning
confidence: 99%